Awareness and knowledge of right to disconnect after work among lecturers in university malaysia kelantan (kota) : a qualitative study - Mohamad Ramzi Ab. Rahim; Muhammad Nizamuddin Shaharudin; Nor Nabihah Zakaria; Nur Syuhada Ahmad (2023)
A job is a group of positions that have similar obligations or basic tasks. In job analysis activities, a job can be occupied by one person, or several people spread out in various places. The objective of this study is to study the awareness and knowledge of right to disconnect after work among lecturers in University Malaysia Kelantan (KOTA). This study examines the impact of disturbances on lecturers at University Malaysia Kelantan, focusing on the right to unplug after work and demand remuneration for labour after hours. Digital technology has enabled remote work, but it also leads to longer workdays. Governments must protect employees and address disconnect laws to ensure work-life balance. The research aims to promote a positive and useful solution for both employees and businesses, preventing recurring issues and promoting a more harmonious work environment.